External drivers of participation in regional collaborative water planning. - Bell, Emily V.; Fencl, Amanda; Mullin, Megan (Policy Studies Journal, 2022)
What drives participation in collaborative planning? How does this vary across different institutional contexts? Public managers must navigate emerging challenges in public service provision; perceived risk and capacity to act can play a pivotal role, shaping managerial behavior. In water management, for example, issues stemming from climate change and water‐intensive growth create new concerns about continued water supply. Strategic decisions may improve local public service provision, but can also have cascading effects on other systems, as water is a mobile—and subtractable—resource. Many public water systems have participated in collaborative planning to overcome collective challenges for this reason, but participation is not feasible for all prospective participants. Using data from administrative records and surveys, we fit a binomial logistic model to examine the roles of capacity and perceived risk among water service providers as drivers of participation in collaborative planning forums. By evaluating this relationship in California and North Carolina, we find similar results across unique institutional contexts: participation in regional water planning is associated with perceived risk to water supply from changing climatic conditions, but not from perceived risk of changing patterns of demand. Also, system capacity—as measured by the size of the population served—corresponds to increased likelihood of participation.